STRATEGI KOMUNIKASI MASYARAKAT SEBATIK PERBATASAN INDONESIA-MALAYSIA DALAM MENGHADAPI PENGARUH LINTAS BUDAYA - Suriyani Suriyani; M. Syukron Anshori (CV. Denasya Smart Publisher, 2025)
This study aims to examine the communication strategies of the people of Sebatik Island in dealing with cross-cultural influences from neighboring Malaysia. As a border region, Sebatik Island has high socio-cultural complexity, inhabited by a multi-ethnic population including Bugis, Tidung, Javanese, and Timorese communities. Using a descriptive qualitative approach and case study methodology, data was collected through interviews, non-participant observation, and documentation. The results of the study indicate that the people of Sebatik use three main strategies in cross-cultural communication based on Communication Accommodation Theory, namely convergence (adjusting communication styles to facilitate interaction, especially in trade activities), divergence (efforts to maintain local cultural identity), and over-accommodation (excessive adjustment, generally occurring among the younger generation who are beginning to lose their attachment to local culture due to the dominance of Malaysian culture). This study confirms that the communication strategies of border communities not only function as a means of interaction, but also as an important strategy in maintaining a balance between adaptation and cultural preservation in multicultural border areas.